Effectiveness of balance training with kinesthetic ability trainer (KAT 2000) in patients with peripheral neuropathic pain: a randomised controlled study - Kerim, Duygu; Uzunkulaoğlu, Aslıhan; Ay, Saime (The European Research Journal, 2019)
Objectives: The aim of this study isto determine the effectiveness of balance training with Kinesthetic Ability Trainer (KAT 2000) in patients with peripheral neuropathic pain related balance disorder. Methods: Sixty patients were included into this controlled prospective study and randomized into either balance exercises group (Group 1) or KAT 2000 exercises group (Group 2). Balance exercises were given to all patients. Also, KAT 2000 balance exercises were given all patients in Group 2 (n = 30). All patients received 45-min individualized training session for three times a week for 4 weeks. Douleur Neuropathique 4 (DN4) questionnaire for neuropathic pain; visual analogue scale (VAS) for pain severity; KAT 2000 for static and dynamic balance; Nottingham Health Profile (NHP) for Quality of Life (QoL) was used. Dynamic balance and mobility also was assessed using the Berg Balance Scale (BBS) and Time Up and Go (TUG) test. Patients were evaluated at baseline and the end of the 4-week exercise program. Results: At the end of the treatment; VAS, BBS, KAT 2000, TUG, NHP, physical activity, NHP pain, NHP social isolation and NHP emotional reactions scores improved significantly in both groups (p < 0.05) except NHP sleep and NHP energy level scores in balance exercises group (p > 0.05). Statistical differences in VAS pain on movement, global assessment of patient, global assessment of doctor, NHP energy level scores were found between the groups (p < 0.05); but there were no statistical difference in VAS at rest, VAS at night, BBS, KAT 2000, TUG, NHP physical activity, NHP pain, NHP sleep, NHP social isolation and NHP emotional reactions scores between the groups (p > 0.05). Conclusion: When combined with the KAT 2000 device, positive effects of balance-coordination exercises on pain on movement and energy level are more evident in patients with peripheral neuropathic pain.